Mobile health information technology for physical activity education during cardiac rehabilitation: a scoping review - Ariyanto, Heri; Ayunitias, Imelda; Patima, Patima; Jamaludin, Thandar Soe Sumaiyah; Nik Mohd Hatta, Nik Noor Kaussar; Shahadan, Siti Zuhaidah; Che Hasan, Muhammad Kamil; Nurumal, Mohd. Said (MAT Journals, 2025)
Introduction: In healthcare delivery system, mobile health is a modern information and communication technology system that facilitates the delivery of nursing care and services to remote locations. Research indicates that mobile health education can enhance physical activity in chronic diseases patients like cardiovacular disease overall. Nonetheless, the effects of mobile health on cardiac disease patients during cardica rehabilitation have yet to be assessed. Objective: To assess the impact of mobile health education on the physical activity levels of cardiac patients during cardica rehabilitation from previous studies. Method: This study used a scoping review method approach. The inclusion criteria encompassed papers published in English from 2019 to 2024. Participants with adult cardiac disease underwent therapies utilising information technology, with outcomes measured in terms of physical activity, the studies employed a randomised controlled trial methodology. Exclusion criteria included psychiatric diseases, literature reviews, systematic reviews, and overviews. This review was performed across four databases: PubMed, Scopus, Wiley, and Emerald Insight. A critical appraisal was performed utilising the Joanna Briggs Institute's Critical Appraisal Checklist. Findings: There are a total of 16 articles included in this review. Three themes emerged in this study. The results indicated that mobile health technology can effectively assist cardiac patients during cardiac rehabilitation by providing tools for real-time monitoring, patient education, and behavioural adjustment. These therapies markedly enhanced physical activity levels and overall quality of life in cardiac patients Conclusion: The educational interventions utilising mobile health, including mobile health, applications, and websites, can enhance the physical activity levels of cardiac patients during cardiac rehabilitation. Thus, mobile health can be utilised in hospitals to deliver nursing care, facilitate education, and remotely monitor the physical activity of cardiac patients during cardiac rehabilitation